2016
DOI: 10.1186/s12939-016-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment, gender and health inequalities among older adults in Catalonia (Spain)

Abstract: BackgroundHealth expectancies vary worldwide according to socioeconomic status (SES), with health disadvantages being evident among lower SES groups. Using educational attainment as a proxy of SES, we seek to identify trends in SES differentials in health by gender, with a particular focus on individuals with low educational attainment in the adult Catalan population (Spain) aged 55 or older.MethodsUsing cross-sectional data for 1994 and 2010-2014 drawn from the Catalan Health Survey, we examined three health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…A negative association between low mental well-being and being female or being older is evident in both rural and urban environments; however, the level of mental well-being is mainly captured by existing differences in health status and personal autonomy [54]. Our findings reveal that the mental risk is aggravated in urban areas.…”
Section: Discussionmentioning
confidence: 60%
“…A negative association between low mental well-being and being female or being older is evident in both rural and urban environments; however, the level of mental well-being is mainly captured by existing differences in health status and personal autonomy [54]. Our findings reveal that the mental risk is aggravated in urban areas.…”
Section: Discussionmentioning
confidence: 60%
“… 24 Pension type and the age at which the participant left full-time education were included as proxy measures for socioeconomic status. 28 29 The simplicity of the ethnic group division chosen was due to low participant numbers in any non-White-British group, particularly in the semirural practices.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are in line with a significant number of studies in high income countries and in developing economies, which have shown a longer LE and a lower proportion of DFLE among women [ 4 , 5 , 7 , 33 39 ]. Previous studies suggest that a lower level of education increases the risk of disability, even at very old ages [ 40 ], and that women are more likely than men to have low levels of education [ 41 43 ]. In our own study, women were less educated (p<0.001), with an average of 5.2 years of education, compared to 6.5 years of education among men.…”
Section: Discussionmentioning
confidence: 99%